211k views
2 votes
Evaluate 3+11t−9u when t=9 and u=11

User Slade
by
4.6k points

2 Answers

4 votes

Answer:


- 19

Explanation:


3 + 11t - 9u = 3 + 11(9) - 9(11) = 3 + 99 - 121 = - 19

User Juan Tarquino
by
4.3k points
2 votes

Answer:

3

Explanation:


3+11t-9u\\t = 9\\u =11\\\\3+11(9) -9(11)\\\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Multiply\:and\:divide\:\left(left\:to\:right\right)}\:11\left(9\right)\::\quad 99\\=3+99-9\left(11\right)\\\\\mathrm{Multiply\:and\:divide\:\left(left\:to\:right\right)}\:9\left(11\right)\::\quad 99\\=3+99-99\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:3+99-99\:\\:\quad 3

User Skan
by
4.7k points